Global gene expression profile in canine mammary carcinomas - Varallo, G. R. [UNESP]; Jardim-Perassi, B. V.; Alexandre, P. A.; Fukumasu, H.; Zuccari, D. A.P.C. (Elsevier, 2019)
Mammary gland tumors are a heterogeneous group of neoplastic diseases. Genetic studies make it possible to determine genetic profiles and identify new molecular markers. The aim of the study was to evaluate the gene expression profile of canine mammary carcinomas and identify potential prognostic markers. Twelve mammary cancer samples from bitches were collected for the evaluation of global gene expression. Microarray assays were performed using commercial kits. Statistical analysis of the microarray was done using moderate t-statistic and adjusted using the Benjamini and Hochberg procedure. Differential connectivity analysis was also performed. Enrichment analyses were conducted using WebGestalt. P-values were calculated using hypergeometric statistics and adjusted using the Benjamini and Hochberg procedure. The HYAL-1 gene was validated using quantitative PCR (qPCR). There were 878 upregulated genes and 821 downregulated genes in the neoplasms studied. Enrichment analysis (individual analysis) identified the HYAL-1 gene as a potential marker of tumorigenesis and tumor recurrence. Differential connectivity analysis demonstrated 262 differentially connected genes.
Keywords: DNA microarray; HYAL-1; Mammary gland; Neoplasms; Prognosis